Research Study On Design And Assessment Of Fire, Life Safty Passive Meaures Of High Rise Mall Building (Journal of Namibian Studies : History Politics Culture, 2023)
In recent years we come across the increased number of fire accidents in the society. To understand the current scenario of this fire behaviour towards the buildings context, a background study was started. The fire accidents numerical and its impacts were analysed. Five buildings affected by fire were selected. The fire influencing factors, the fire safety and life safety measures working conditions were studied. The fire accidents numerical data study was indicated that,” The numbers of fire accidents are increasing in recent past years”. The fire affected buildings study was indicated that,” Few buildings were not provided with the fire safety measures and few buildings were provided with fire safety measures but they were not working at the time of fire accident. This background study results raised the question and the research problem was identified. The aim of the research was to “evaluate the heat resistance capability of building elements” The  City area was selected as study area. The commercial category mall type buildings were selected as sample from this study area. study area  documentation source was used for sample selection. Stratified sampling method was followed. These research elements and the research problem question gave a refined research problem statement as “Evaluation of Fire and Life Safety Passive Measures of Mall Buildings”. This topic related information was referred from the available sources. The inadequate with missing information were found based on this topic. The hypothesis statement was framed based on the background study and the review of literature. The objectives of research were ”To assure the full fledged implementation of fire safety measures, to assure the planning, structural stability efficiency of the measures, to assure to avoid the internal, external fire spread, to assure the evacuation within the time limit and to assure life safety, property safety of the people in side”. All were deal  with fire and life safety passive measures. The quantitative applied research type was used for this research requirements preparation.